সাচুং-ঙম্বা (পামহৈবগী ফন্বাললাল) - Shamchetshaba, M.K. (Shalungpham Kala Memorial Manuscript Library, 1996)
This book is a historical account of the Meitiei King Pamheiba.
Shaachungamba
Keywords: Manipuri; সাচুং-ঙম্বা (পামহৈবগী ফন্বাললাল); Shaachungamba; No Information; Manipuri; Manipuri